CaHSL1 Acts as a Positive Regulator of Pepper Thermotolerance Under High Humidity and Is Transcriptionally Modulated by CaWRKY40 - Guan, Deyi; Yang, Feng; Xia, Xiaoqin; Shi, Yuanyuan; Yang, Sheng; Cheng, Wei; He, Shuilin (Frontiers in Plant Science, 2018)
Pepper (Capsicum annuum) is an economically important vegetable and heat stress can severely impair pepper growth, development, and productivity. The molecular mechanisms underlying pepper thermotolerance are therefore important to understand but remain elusive. In the present study, we characterized the function of CaHSL1, encoding a HAESA-LIKE (HSL) receptor-like protein kinase (RLK), during the response of pepper to high temperature and high humidity (HTHH). CaHSL1 exhibits the typical structural features of an arginine-aspartate RLK. Transient overexpression of CaHSL1 in the mesophyll cells of Nicotiana benthamiana showed that CaHSL1 localizes throughout the cell, including the plasma membrane, cytoplasm, and the nucleus. CaHSL1 was significantly upregulated by HTHH or the exogenous application of abscisic acid but not by Ralstonia solanacearum inoculation. However, CaHSL1 was downregulated by exogenously applied salicylic acid, methyl jasmonate, or ethephon. Silencing of CaHSL1 by virus-induced gene silencing significantly was reduced tolerance to HTHH and downregulated transcript levels of an associated gene CaHSP24. In contrast, transient overexpression of CaHSL1 enhanced the transcript abundance of CaHSP24 and increased tolerance to HTHH, as manifested by enhanced optimal/maximal photochemical efficiency of photosystem II in the dark (Fv/Fm) and actual photochemical efficiency of photosystem II in the light. In addition, CaWRKY40 targeted the promoter of CaHSL1 and induced transcription during HTHH but not in response to Ralstonia solanacearum. All of these results suggest that CaHSL1 is directly modulated at the transcriptional level by CaWRKY40 and functions as a positive regulator in the response of pepper to HTHH.